Classroom Climate in Remote Schools: Inhibiting Factors and Pedagogical Solutions Through Formative Assessment and Contextual Learning - Rince Jalla Wabang; Maria Rosalinda Talan; Septoriana Maria Nino (LPPM Institut Pendidikan Nusantara Global, 2026)
The purpose of this study is to examine the factors that hinder the classroom climate in remote schools and to explore formative assessment and contextual learning as pedagogical solutions. This study employs a literature review method by analyzing various relevant scientific sources regarding classroom climate, remote schools, formative assessment, and contextual learning. The outcomes of the study indicate that barriers to classroom climate in remote schools include limited educational resources, a shortage of teaching staff, students’ socioeconomic conditions, inadequate school physical environments, as well as socio-cultural issues and school governance. These barriers outcome in low student engagement, suboptimal learning interactions, and a weak conducive learning atmosphere. The connection of resources to learners’ real-life events as well as settings is contextual learning, and this study also shows how formative assessment is useful for teachers to continuously identify student needs, achievements, and obstacles that may challenge the students' learning. Hence, formative assessment and contextual learning can be considered as two complementary pedagogic solutions in establishing a more adaptive, participatory and meaningful classroom climate at remote schools.